Pengaruh Pajak Daerah, Retribusi Daerah dan Laba Badan Usaha Milik Daerah di (BUMD) Terhadap Pertumbuhan Ekonomi Kabupaten Aceh Utara - Muchsal Mina; Ratna Ratna (LPPM UNIMAL, 2020)
This study aims to determine how much influence local taxes, regional levies and profits of regional-owned enterprises on economic growth in North Aceh Regency. The data used in this study is secondary data sourced from the North Aceh Central Bureau of Statistics 2005-2017. The data analysis method used in this study is multiple linear regression methods. With the help of Eviews 10 the results of the research partially show that regional taxes have a negative and significant effect on economic growth in North Aceh District. regional retribution does not affect and negatively affect economic growth in North Aceh Regency, and the profits of regionally owned enterprises have a positive and significant effect on economic growth in North Aceh District. The results of the tests carried out jointly are known that Regional Taxes, Regional Levies and profits of Regionally Owned Enterprises have a joint effect on Economic Growth in North Aceh Regency at 0.8133 (8133%).Keyword : Regional Taxes, Regional Levies, Owned Enterprise Profits Regions, Economic Growth.